The MUC5B Promoter Polymorphism Associates With Severe COVID-19 in the European Population - van Moorsel, Coline H. M.; van der Vis, Joanne J.; Duckworth, Anna; Scotton, Chris J.; Benschop, Claudia; Ellinghaus, David; Ruven, Henk J. T.; Quanjel, Marian J. R.; Grutters, Jan C. (Frontiers in Medicine, 2021)
Background: Diversity in response on exposure to severe acute respiratory syndrome coronavirus 2 may be related to the innate immune response in the elderly. The mucin MUC5B is an important component of the innate immune response and expression levels are associated with the MUC5B promoter polymorphism, rs35705950. The high expressing T-allele is a risk allele for the non-infectious aging lung disease idiopathic pulmonary fibrosis (IPF). We investigated if MUC5B rs35705950 associates with severe COVID-19. Methods: In this retrospective candidate gene case-control study we recruited 108 Dutch patients (69% male, median age 66 years, 77% white) requiring hospitalization for COVID-19 (22% ICU stay, 24% died). For validation, genotypes were obtained from the UK-Biobank (n = 436, 57% male, median age 70 years, 27% died), for replication data from the severe COVID-19 GWAS group from Italy (n = 835) and Spain (n = 775) was used, each with a control cohort (n = 356,735, n = 1,255, n = 950, respectively). MUC5B association analysis was performed including adjustment for age and sex. Results: The rs35705950 T-allele frequency was significantly lower in Dutch white patients (n = 83) than in controls (0.04 vs. 0.10; p = 0.02). This was validated in the UK biobank cohort (0.08 vs. 0.11; p = 0.001). While age and sex differed significantly between cases and control, comparable results were obtained with age and sex as confounding variables in a multivariate analysis. The association was replicated in the Italian (p = 0.04), and Spanish (p = 0.03) case-control cohorts. Meta-analysis showed a negative association for the T-allele with COVID-19 (OR = 0.75 (CI: 0.67–0.85); p = 6.63 × 10−6). Conclusions: This study shows that carriage of the T-allele of MUC5B rs35705950 confers protection from development of severe COVID-19. Because the T-allele is a known risk allele for IPF, this study provides further evidence for the existence of trade-offs between optimal mucin expression levels in the aging lung.